1998
DOI: 10.1111/j.1467-8624.1998.tb06132.x
|View full text |Cite
|
Sign up to set email alerts
|

Déjà Vu All Over Again: Effects of Reenactment on Toddlers' Event Memory

Abstract: Four experiments examined (1) whether reenactment improves 18-month-olds' event memory, (2) how effects of reenactment are affected by the time at which the reenactment occurs, (3) whether timing of reenactment affects recall over very long periods of time, and (4) how partial reenactment affects recall. Children were trained to perform 8 novel activities in a laboratory playroom, returned to the playroom 15 min to 8 weeks later to reenact the activities, and were tested for recall of the original activities 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 37 publications
1
19
1
Order By: Relevance
“…Although our current understanding of memory reactivation in human infants is based largely on operant conditioning procedures, a growing body of research, including the data reported here, has shown that the phenomenon of memory reactivation can be examined with other memory paradigms commonly used with infants (Bahrick et al, 1997;Barr, Marrott, & RoveeCollier, 2003;Barr, Vieira, & Rovee-Collier, 2002;Cornell, 1979;Hayne, Barr, & Herbert, 2003;Hudson & Sheffield, 1998. Thus, despite the common claim that operant conditioning procedures and VRM procedures measure different kinds of memory in human infants, many of the findings obtained using these two different procedures are remarkably similar (Hayne, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although our current understanding of memory reactivation in human infants is based largely on operant conditioning procedures, a growing body of research, including the data reported here, has shown that the phenomenon of memory reactivation can be examined with other memory paradigms commonly used with infants (Bahrick et al, 1997;Barr, Marrott, & RoveeCollier, 2003;Barr, Vieira, & Rovee-Collier, 2002;Cornell, 1979;Hayne, Barr, & Herbert, 2003;Hudson & Sheffield, 1998. Thus, despite the common claim that operant conditioning procedures and VRM procedures measure different kinds of memory in human infants, many of the findings obtained using these two different procedures are remarkably similar (Hayne, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…First, studies of memory reactivation have focussed primarily on changes that occur over the first year of life; substantially less is known about agerelated changes in memory reactivation that occur during the second half of the infancy period (but see Hsu et al, 2005). Second, although memory reactivation has been documented in other memory paradigms, much of this work has focussed on infants of a single age rather than two or more age groups (e.g., Hudson & Sheffield, 1998. As such, the generality of the developmental principles of memory retrieval derived from studies of operant conditioning procedures is not known.…”
mentioning
confidence: 99%
“…He defined retrieval difficulty in terms of the time since the last retrieval. This hypothesis has since been confirmed in studies with normal adults (Landauer & Bjork, 1978;Schmidt & Bjork, 1992), amnesic adults (Camp, Foss, O'Hanlon, & Stevens, 1996;Wilson, 1989), school-age children (Rea & Modigliani, 1985), toddlers (Hudson & Sheffield, 1998), and 3-monthold infants (Hartshorn, Wilk, Muller, & Rovee-Collier, 1998b;Rovee-Collier, Evancio, & Earley, 1995;RoveeCollier, Greco-Vigorito, & Hayne, 1993). Although retention of the newly acquired memory is superior when successive retrievals are further apart, only one study has reported data suggesting that the same principle may describe retention of a reactivated memory.…”
mentioning
confidence: 86%
“…Some of the phenomena explained using the time window concept are categorization, memory modification and the spacing effect (Rovee-Collier, 1995). For the spacing effect, studies using the time window concept have found that repetitions that occur later in the time window lead to a task being remembered longer than repetitions that occur earlier in the time window; however, if the repetition is outside the time window, even if it is only a single day, it is as if the infant is encountering it for the first time (Rovee-Collier et al, 1995; Hartshorn et al, 1998b; Hudson and Sheffield, 1998; Galluccio and Rovee-Collier, 2006). …”
Section: The Spacing Effect In Skill-related Tasksmentioning
confidence: 99%